Evaluation of integrated modular & traditional curriculum learning environment in medical education - Uzma Kausar; Muhammad Sohail Anjum Noor; Muhammad Usama Sohail; Muhammad Hamza Rana (Journal of University Medical & Dental College)
ABSTRACT: